Genotype‐directed, dose‐finding study of irinotecan in cancer patients with UGT1A1*28 and/or UGT1A1*6 polymorphisms - Taroh Satoh; Takashi Ura; Yasuhide Yamada; Kentaro Yamazaki; Toshimasa Tsujinaka; Masaki Munakata; Tomohiro Nishina; Shu Okamura; Taito Esaki; Yasutsuna Sasaki; Wasaburo Koizumi; Yoshihiro Kakeji; et al. (2011)
Irinotecan-induced severe neutropenia is associated with homozygosity for the UGT1A1*28 or UGT1A1*6 alleles. In this study, we determined the maximum-tolerated dose (MTD) of irinotecan in patients with UGT1A1 polymorphisms. Patients who had received chemotherapy other than irinotecan for metastatic gastrointestinal cancer were enrolled. Patients were divided into three groups according to UGT1A1 genotypes: wild-type (*1/*1); heterozygous (*28/*1, *6/*1); or homozygous (*28/*28, *6/*6, *28/*6). Irinotecan was given every 2 weeks for two cycles. The wild-type group received a fixed dose of irinotecan (150 mg/m(2)) to serve as a reference. The MTD was guided from 75 to 150 mg/m(2) by the continual reassessment method in the heterozygous and homozygous groups. Dose-limiting toxicity (DLT) and pharmacokinetics were evaluated during cycle 1. Of 82 patients enrolled, DLT was assessable in 79 patients (wild-type, 40; heterozygous, 20; and homozygous, 19). Dose-limiting toxicity occurred in one patient in the wild-type group, none in the heterozygous group, and six patients (grade 4 neutropenia) in the homozygous group. In the homozygous group, the MTD was 150 mg/m(2) and the probability of DLT was 37.4%. The second cycle was delayed because of neutropenia in 56.3% of the patients given the MTD. The AUC(0-24 h) of SN-38 was significantly greater (P < 0.001) and more widely distributed in the homozygous group. Patients homozygous for the UGT1A1*28 or UGT1A1*6 allele can receive irinotecan in a starting dose of 150 mg/m(2), but many required dose reductions or delayed treatment in subsequent cycles. UMIN Clinical Trial Registration number: UMIN000000618.